Is Low Serum Vitamin D Associated with Early Dental Implant Failure? A Retrospective Evaluation on 1625 Implants Placed in 822 Patients - Francesco Mangano; Carmen Mortellaro; Natale Mangano; Carlo Mangano (Hindawi Limited, 2016)
Aim. To investigate whether there is a correlation between early dental implant failure and low serum levels of vitamin D. Methods. All patients treated with dental implants in a single centre, in the period 2003-2015, were considered for enrollment in this study. The main outcome was early implant failure. The influence of patient-related variables on implant survival was calculated using the Chi-square test. Results. 822 patients treated with 1625 implants were selected for this study; 27 early failures (3.2%) were recorded. There was no link between gender, age, smoking, history of periodontitis, and an increased incidence of early failures. Statistical analysis reported 9 early failures (2.2%) in patients with serum levels of vitamin D > 30 ng/mL, 16 early failures (3.9%) in patients with levels between 10 and 30 ng/mL, and 2 early failures (9.0%) in patients with levels <10 ng/mL. Although there was an increasing trend in the incidence of early implant failures with the worsening of vitamin D deficiency, the difference between these 3 groups was not statistically significant (P=0.15). Conclusions. This study failed in proving an effective link between low serum levels of vitamin D and an increased risk of early implant failure. Further studies are needed to investigate this topic.